Pharmacists' role in harm reduction: a survey assessment of Kentucky community pharmacists' willingness to participate in syringe/needle exchange - Amie Goodin; Amanda Fallin-Bennett; Traci Green; Patricia R. Freeman (BMC, 2018)
Abstract Background Pharmacists' role in harm reduction is expanding in many states, yet there are limited data on pharmacists' willingness to participate in harm reduction activities. This study assessed community pharmacists' willingness to participate in one harm reduction initiative: syringe/needle exchange. Methods In 2015, all Kentucky pharmacists with active licenses were emailed a survey that examined attitudes towards participation in syringe/needle exchange. Response frequencies were calculated for community pharmacist respondents. Ordinal logistic regression estimated the impact of community pharmacist characteristics and attitudes on willingness to provide clean needles/syringes to people who inject drugs and to dispose of used syringes/needles, where both dependent variables were defined as Likert-type questions on a scale of 1 (not at all willing) to 6 (very willing). Results Of 4699 practicing Kentucky pharmacists, 1282 pharmacists responded (response rate = 27.3%); the majority (n = 827) were community pharmacists. Community pharmacists were divided on willingness to provide clean needles/syringes, with 39.1% not willing (score 1 or 2 of 6) and 30% very willing (score 5 or 6 of 6). Few were willing to dispose of used needles/syringes, with only 18.7% willing. Community pharmacists who agreed that pharmacists could have significant public health impact by providing access to clean needles expressed 3.56 times more willingness to provide clean needles (95% CI 3.06-4.15), and 2.04 times more willingness to dispose of used needles (95% CI 1.77-2.35). Chain/supermarket pharmacists (n = 485, 58.6% of community pharmacies) were 39% less likely to express willingness to dispose of used needles (95% CI 0.43-0.87) when compared with independent community pharmacists (n = 342, 41.4% of community pharmacies). Independent pharmacists reported different barriers (workflow) than their chain/supermarket pharmacist colleagues (concerns of clientele). Conclusions Kentucky community pharmacists were more willing to provide clean needles than to dispose of used needles. Strategies to mitigate barriers to participation in syringe/needle exchange are warranted.